Elder financial abuse experience: a qualitative study from the perspective of older persons in Malaysia - Che Amani, Nor Fadhilah; Kahar, Rojanah; Ibrahim, Rahimah; Hasbullah @ Abdullah, Muslihah (Human Resource Management Academic Research Society, 2021)
The underreporting incidents of financial exploitation of older persons committed by family members in Malaysia is a genuine concern. This study explores older adults’ experience of financial abuse by family members, the dynamics of their relationship, and how older people respond to this experience in Malaysia. The study was conducted using a phenomenology study design via in-depth interviews of eight older adults who were purposively sampled using snowball sampling. NVivo 12 analysis software was used to perform the thematic analysis. Seven main themes were identified: cultural expectation and tolerance of abuse, negative well-being, family comes first, helplessness, coping strategies, positive reappraisal, and self-reflection. The themes demonstrate the interactions among the components of experiences of older adults coping with financial abuse by family members and how they chose to respond. The results reveal the inadequacy of protections available to older adults in Malaysia in the reporting process, laws, and policy. These results suggest for authorities to consider dilemmas faced by older victims of financial abuse, especially with regard to underreporting. A clearer understanding of social realities will help improve social and legal protection frameworks for victims of financial abuse involving family members in Malaysia.